Spindle Cell Hemangioendothelioma: Rare Clinical Entity - Das, Kapil Dev (Indian J Dermatol, 2015)
Spindle-cell hemangioendothelioma (SCHE) comprise a rare subset of vascular tumors, and here, we describe such a case and review the clinical presentation, patho-physiology, differential diagnosis of these tumors to promote early identification and discussion guidance. A 25-years-old male patient presented with multiple painful elevated swellings of both left upper and lower extremities for last 15 years without any systemic involvement. After excluding close differential diagnosis by relevant investigations an excisional biopsy was performed. Based on clinical, radiological and histopathological findings, diagnosis of SCHE was made and full thickness excision and skin grafting were performed. The case is reported due to its rarity and adds our knowledge to the existing literature.